The Relationship Between Parenting Styles and Adolescent Sexual Behavior - Setiani, Ermy; Sulaiman, Lalu; Sismulyanto, Sismulyanto (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study aims to investigates the correlation between parenting styles and adolescent sexual behavior at SMA Negeri 3 Mataram using an observational analytic design with a cross-sectional approach. Data were collected from 69 11th-grade social science students via a questionnaire assessing parenting styles and sexual behavior. Results indicated that (1) 59.4% of respondents experienced permissive parenting, while 40.6% encountered democratic parenting; (2) respondents who have permissive parenting, 5.8% demonstrated negative sexual behavior, in contrast to the uniformly positive behavior observed in adolescents with democratic parenting; (3) the results of Fisher's exact test are a significance value of 0.141, indicating no statistically significant relationship between parenting styles and adolescent sexual behavior; (4) trend suggests that democratic parenting, which balances freedom and control, is associated with positive adolescent sexual behavior. Thus, these findings highlight the importance of promoting democratic parenting and comprehensive sexual education to reduce risky behaviors. Recognizing cultural nuances and enhancing parental involvement are essential for effective adolescent sexual health prevention strategies.